PHOTOACTIVE TUNGSTEN-OXIDE NANOMATERIALS FOR WATER-SPLITTING - Shabdan, Yerkin; Markhabayeva, Aiymkul; Bakranov, Nurlan; Nuraje, Nurxat (MDPI, 2020)
This review focuses on tungsten oxide (WO3) and its nanocomposites as photoactive nanomaterials for photoelectrochemical cell (PEC) applications since it possesses exceptional properties such as photostability, high electron mobility (~12 cm2 V −1 s −1 ) and a long hole-diffusion length (~150 nm). Although WO3 has demonstrated oxygen-evolution capability in PEC, further increase of its PEC efficiency is limited by high recombination rate of photogenerated electron/hole carriers and slow charge transfer at the liquid–solid interface. To further increase the PEC efficiency of the WO3 photocatalyst, designing WO3 nanocomposites via surface–interface engineering and doping would be a great strategy to enhance the PEC performance via improving charge separation. This review starts with the basic principle of water-splitting and physical chemistry properties of WO3, that extends to various strategies to produce binary/ternary nanocomposites for PEC, particulate photocatalysts, Z-schemes and tandem-cell applications. The effect of PEC crystalline structure and nanomorphologies on efficiency are included. For both binary and ternary WO3 nanocomposite systems, the PEC performance under different conditions—including synthesis approaches, various electrolytes, morphologies and applied bias—are summarized. At the end of the review, a conclusion and outlook section concluded the WO3 photocatalyst-based system with an overview of WO3 and their nanocomposites for photocatalytic applications and provided the readers with potential research directions.
Keywords: WO3; nanocomposites; heterostructures; water-splitting; oxygen evolution; Type of access: Open Access